Determinan Niat Pengajuan Pembiayaan Mudharabah pada BMT NURUL JANNAH GRESIK - Friska Mega Puspitasari; Moh. Qudzi Fauzi (Universitas Airlangga, 2018)
This study aims to determine the effect of collateral flexibility, quality of service, and sharia compliance on intention of filing of mudharabah financing at BMT Nurul Jannah Gresik. This study used quantitative method and sample used is some community members who reside around BMT Nurul Jannah Gresik. Sampling technique used is purposive sampling. Analysis technique used is multiple linear regression analysis. Results showed that variable of collateral flexibility, quality of service, and sharia compliance both simultaneously and partially has significant effect on intention of filing of mudharabah financing at BMT Nurul Jannah Gresik. Percentage of contributions of the three variables on the intention of filing of mudharabah financing amounted to 62% and the balance of 38% influenced by other factors which is not included in this study. REFERENCESAgag, Gooma & El-Masry, Ahmed A. 2016. Understanding condumer intention to participate in online travel community and effects on consumer intention to purchase travel online and WOM: An integration of innovation diffusion theory and TAM with trust. Journal of Computers in Human Behavior, 60, 97-111.An-Nawawi, Yahya bin Syarif. 2007. Syarah Arba’in Nawawi. Solo : Pustaka Arafah.Arslan, Muhammad. 2014. Impact of Brand Image and Service Quality on Consumer Purchase Intention: A Study of Retail Store in Pakistan. Research on Humanities and Social Scienes. Vol. 4, no.22.Awami, Shofia Nur. 2009. Peranan Lembaga Keuangan Mikro dan Kontribusi Kredit terhadap Pendapatan Kotor UKM Rumah Tangga setelah menjadi Kreditur (Studi Kasus BMT Muamalat). Jurnal Ilmu Pertanian. Vol 5, no.2.Azra, Azyumardi. 2003. Berderma untuk Semua. Jakarta : PT. Mizan Pustaka.Departemen Agama RI. 1998. Al-Qur’an dan Terjemahnya. Jakarta : Al-Hidayah Surabaya.Fatwa DSN MUI No: 07/DSN-MUI/IV/2000 Tentang Pembiayaan Mudharabah (Qiradh).Ghozali, Imam. 2012. Aplikasi Analisis Multivariate dengan Program IBM SPSS 20. Semarang : Badan Penerbit Universitas Diponegoro.Huda, Nurul dan Mohamad Heykal. 2010. Lembaga Keuangan Islam : Tinjauan Teoritis dan Praktis. Jakarta : Kencana.Ilmi, Makhalul. 2002. Teori dan Praktek lembaga Keuangan Mikro Syariah. Yogyakarta : UII Press.Kasmir. 2004. Manajemen Perbankan. Jakarta : PT. RAJA Grafindo Persada.Mauludin, Hanif. 2004. Ananlisis Kualitas Pelayanan, Pengaruhnya Terhadap Image (Studi Pada Penderita RSUD DR.R. Koesma Tuban). Jurnal Penelitian Akuntansi, Bisnis, dan Manajemen. Vol. 7, no.1. Yogyakarta : Fakultas Syari’ah dan Hukum Universitas Islam Negeri Sunan Kalijaga.Noviandi, Barus Aulia. 2009. Analisis Faktor-Faktor Pengambilan Pembiayaan dan Penilaian Efektifitas Pembiayaan Syariah Bagi Usaha Kecil pada BMT Dana Insani Kabupaten Gunung Kidul Propinsi Yogyakarta. Skripsi. Bogor : Fakultas Pertanian Institut Pertanian Bogor.Oxford Advanced Leaner’s Dictionary. 2005. Oxford : Oxford University Press.Parasuraman, Zeithaml, dkk. 1990. Five Imperatives for Improving Servive Quality. Sloan Management Review.Perwataatmadja, Karnaen Anwar dan Henri Samsul Bahri Tanjung. 2007. Bank Syariah (Teori, Praktik, dan Peranannya), Cet.I. Jakarta : Celestial Publising.Puskopsyah. 2014. Lembaga Keuangan Mikro Syariah, (Online), http://www.puskopsyahbmtjateng.com/. (Diakses tanggal 9 Juni 2016).Ridwan, Muhammad. 2004. Manajemen Baitul Maal Wat Tamwil (BMT). Yogyakarta : UII Press.Rosmalinda, Upia. 2015. Studi Kritik Prinsip Kehati-Hatian Dalam Perspektif Pencegahan Pembiayaan Bermasalah Pada Bank Syariah. Jurnal Universitas Muhammadiyah Metro. Vol 11, no.2.Ruwati dan Pandi Afandi. 2014. Persepsi Nasabah Pada Aspek 5C Untuk Menentukan Kelayakan Pemberian Kredit Pada Nasabah PT BPR Nusamba Ampel Cabang Salatiga. Jurnal STIE Semarang. Vol 6, no.1: 59-64.Santoso, Singgih. 2011. Mastering SPSS Versi 19. Jakarta : PT Elex Media Komputindo.Sheeran, Paschal. 2011. Intention-Behavior Relations: A Conceptual and Empirical Review. European Review of Social Psychology.Sudarsono, Heri. 2003. Bank dan Lembaga Keuangan Syariah. Yogyakarta : Ekonisia.Sutarno. 2004. Aspek-Aspek Hukum Perkreditan Pada Bank. Bandung : Alfabeta.Sutedi, Andrian. 2009. Perbankan Syariah Tinjauan dan Beberapa Segi Hukum. Bogor : Ghalia Indonesia.Ummah, Ghazirah Abdi. 2002. Fathul Baari syarah Shahih Al Bukhari. Jakarta : Pustaka Azzam.White, Andrew. 2013. Singapura Apresiasi Kiprah BMT di Indonesia, (Online), http://www.republika.co.id/berita/ekonomi/keuangan/13/10/26/mv8yxl-singapura-apresiasi-kiprah-bmt-di-indonesia. (Diakses 4 Juni 2016).Yunus, Muhammad. 2007. Bank Kaum Mikin. Tangerang Selatan : CV. Marjin Kiri.